PSYCHOLOGICAL EVALUATION DEVICE, PSYCHOLOGICAL EVALUATION METHOD, PROGRAM, ACCELERATION MEASUREMENT SYSTEM, AND ACCELERATION MEASUREMENT METHOD - ITAKURA Naoaki; HANADA Takeshi; AMADA Chisato; MIZUNO Tota; NAKASHIMA Taiyo; HORIE Nobuhiko (2021)
The interest that a subject has in content used together with a terminal 100 held by the subject is inferred. Acceleration data obtained by an acceleration sensor built in the terminal 100 is acquired, and the acquired acceleration data is subjected to frequency analysis to obtain the acceleration of the terminal in the gravity direction. By obtaining the acceleration of the terminal in the gravity direction, the interest that the subject has in the content can be inferred, for example, from the integral value of the frequency components of the acceleration in the gravity direction obtained by the frequency analysis. L'intérêt qu'un sujet présente pour un contenu utilisé conjointement avec un terminal 100 tenu par le sujet est déduit. Des données d'accélération obtenues par un capteur d'accélération intégré dans le terminal 100 sont acquises, et les données d'accélération acquises sont soumises à une analyse de fréquence pour obtenir l'accélération du terminal dans la direction de la gravité. En obtenant l'accélération du terminal dans la direction de la gravité, l'intérêt que le sujet présente pour le contenu peut être inféré, par exemple, à partir de la valeur intégrale des composantes de fréquence de l'accélération dans la direction de la gravité obtenue par l'analyse de fréquence. 被験者が保持した端末１００と一体に利用されるコンテンツの、被験者の興味を推定する。端末１００に内蔵された加速度センサで得られた加速度データを取得し、取得した加速度データを周波数解析して端末の重力方向の加速度を得る。端末の重力方向の加速度を得ることで、例えば、周波数解析で得られた重力方向の加速度の各周波数成分の積分値から、被験者のコンテンツに対する興味を推定することができる。